2020
DOI: 10.1152/japplphysiol.00369.2020
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational effects on intracranial pressure and blood flow regulation in young men: a potential shunting role for the external carotid artery

Abstract: We sought to determine whether gravity-induced changes in intracranial pressure influence cerebral blood flow regulation. Accordingly, nine young healthy men were studied while supine (0 degree) and during mild changes in hydrostatic pressure induced by head-up tilt at +20 and +10 degrees (HUT+20 and HUT+10) and head-down tilt at -20 and -10 degrees (HDT-20, HDT-10). Blood flows were measured in the internal and external carotid, and vertebral arteries (ICA, ECA and VA). Intraocular pressure (IOP) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…Previous reports have found that steady-state CBF was preserved during −10° HDT for 5–10 min ( 10 , 16 ) consistent with the present results of no change in mean MCAV during −10° HDT. In addition, Ogoh et al reported no changes in internal carotid artery blood flow during −10° and −20° HDT for 10 min ( 34 ). The present study showed no change in steady-state CBF during −30° HDT for 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have found that steady-state CBF was preserved during −10° HDT for 5–10 min ( 10 , 16 ) consistent with the present results of no change in mean MCAV during −10° HDT. In addition, Ogoh et al reported no changes in internal carotid artery blood flow during −10° and −20° HDT for 10 min ( 34 ). The present study showed no change in steady-state CBF during −30° HDT for 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…Hirasawa et al [71] reported a plateau in ICA flow 60 s into a 120-s unilateral static leg contraction at 30% of MVC. External carotid artery blood flow, however, demonstrated a continual rise, concurrent with small increases in MAP in the later stages, indicative of a potentially protective mechanism by directing flow extracranially during hypertension [83]. Whether this persists during dynamic exercise with larger increases in MAP is unknown, and difficult to assess with current imaging methodologies (see Measurement challenges and considerations).…”
Section: Static Resistance Exercisementioning
confidence: 99%
“…the angle of tilt applied differ from that in the previous study (Ogoh et al, 2020), the possibility should be considered that the changes in the facial tissue microcirculation might differ from those in the macrocirculation at the external carotid artery level, even for the same extracranial circulation. However, the previous study by Ogoh et al (2020) and the present study together suggested that the extracranial tissue circulation varied with steeper HDT.…”
Section: Cheek Sbf and Extracranial Circulationmentioning
confidence: 72%
“…Blood flow regulation in the internal and external carotid arteries is reported to differ during gravitational changes (Ogoh et al, 2020). the angle of tilt applied differ from that in the previous study (Ogoh et al, 2020), the possibility should be considered that the changes in the facial tissue microcirculation might differ from those in the macrocirculation at the external carotid artery level, even for the same extracranial circulation. However, the previous study by Ogoh et al (2020) and the present study together suggested that the extracranial tissue circulation varied with steeper HDT.…”
Section: Cheek Sbf and Extracranial Circulationmentioning
confidence: 75%